Penerapan Perencanaan Pajak Penghasilan Pasal 21 Sebagai Upaya Penghematan Pajak Penghasilan Badan PT Z - Ani Rahayu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
Objective – to find out the relationship between Article 21 Income Tax planning and Corporate Income Tax savings. Design/methodology/approach – the type of research is descriptive qualitative. Findings - planning the calculation of Income Tax (PPh) Article 21 by comparing 3 different methods where it turns out that the gross up method is quite influential on the savings of PT Z's Corporate Income Tax so that there is a savings of Rp. 24.199.674 Limitations/implications – this Article 21 Income Tax plan only takes into account the tax object on the gross income of permanent employees and excluded other Article 21 Income Tax objects